Aplikasi Lembaga Perlindungan Anak Jatim berbasis Website - Hanny Kristian Kurniawan; Kristo Radion Purba (Jurnal Infra, 2017)
At this time, certainly no stranger to hear their child abuse, whether it be physical, sexual or physikologi. All of it is a form of child abuse that is not supposed to happen. Things that interfere with the development of each child tiap-, both mentally and physically. Increasingly horrific atrocities committed by the offender against children.Limitations of the reporting media, time constraints, many thought, also became one of only constraint in reporting child abuse. Surabaya, advanced city is also child abuse often occur, even not infrequently victims are reluctant to report it to the authorities. Child Protection Agency in Surabaya East Java which is not at all know it is located and how to report it, so that a lack of success in handling child abuse cases in East Java.Therefore made a media complaints or reporting child abuse based website, which can be done online and does not take long to transmit evidence of child abuse. Males motion constraints, did not have much time, transport constraints, constraints difficulty of reporting. Even for those who do not understand the Child Protection Agency in East Java was able to understand and easy to report child abuse.From the test results, this application can help users to understand the importance of reporting child abuse to Child Protection Institution of East Java, fostering good relationships with the Parent, increase knowledge of child abuse and help users to do counseling with Child Protection Institution of East Java.